Merkel Cell Carcinoma: Interdisciplinary Management of a Rare Disease - Sven Schneider; Dietmar Thurnher; Boban M. Erovic (Journal of Skin Cancer)
Background. The goal of this paper is to review contemporary multidisciplinary treatment with reference to Merkel cell carcinoma. Management of this rare but highly aggressive skin cancer is a complex undertaking that necessitates an understanding of its etiology, epidemiology, clinical presentation, and the coordinated work of several clinical specializations. Recent Findings. The contemporary literature employs a multidisciplinary approach to achieve the best patient's treatment. Conclusion. This paper presents an algorithm for contemporary management for the rare and aggressive Merkel cell carcinoma. Multidisciplinary approach in a tumor center provides high-quality care for patients with Merkel cell carcinoma.